THE BEHAVIOR OF INTEREST RATE AT EARLY REPAYMENT OF DEBT IN THE GENERALIZED CREDIT TRANSACTIONS - Y. F. Kasimov; A. N. Kolesnikov (Научный вестник МГТУ ГА, 2017)
The patterns of early repayment in multi-period credit transactions from internal rate of return view are analyzed in this article. At the early repayment of debt a borrower pays to a moneylender a sum of money equal to current balance (the status of credit account). After that the contracted is finished. However in reality the borrower pays to a moneylender a sum of all unpaid payment, and the moneylender in his turn gives back to the borrower a part of this sum. To calculate it the rule 78 is often used. The borrower’s extra costs connected with the application of the rule 78 may be considered as extra punitive sanctions at the early repayment of debt. However the sanction value achieves its maximum when the maturity is between 57 and 66 percent of the total of the loan term what is contrary to good sense.The situation changes drastically if the sanctions are watched from the point of view of the internal interest rate, which may also determine the cost of credit. In this case, as it was shown, the interest rate can greatly exceed the originally announced rate. The value of this exceedance monotonously increases with the increase in the number of outstanding payments in case of early repayment of the debt. From this it follows that the sanctions associated with the use of rule 78, monotonically increase too. This is consistent with the idea of sanctions from the lender's perspective. Namely, the sanctions must become the smaller, the less time remains prior to the initial date of repayment of the loan.